1999
DOI: 10.31421/ijhs/5/1-2/19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different sources of resistance for breeding powdery mildew resistant grapevine varieties

Abstract: The appearance of resistance to powdery mildew was investigated on seedling progenies of interspecific crossings. Hybrids of American and East-Asian wild species and one Vitis vinifera variety (Janjal kara) were used as source of resistance in the crossings. The resistance of foliage and of berries were tested in the field at the time of vintage. The degree of resistance was ranked into six classes. In American and Asian hybrid derivatives there were few highly resistant progenies, but in the hybrids of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…In general, results of the experiments indicated that 18.18% of tested varieties were immune to the disease, 13.63% were highly resistant, 9.10% were resistant, 9.10% were tolerant, 36.36% were susceptible and 13.63% highly susceptible to powdery mildew disease (Table 1). Results of our study and the differences in the reaction of varieties to powdery mildew disease are in agreement with those of previous studies (Barker et al, 2005;Eibach et al, 2007;Korbuly, 1999;Li, 1993;Wan et al, 2007). Voytovich (1987), Wang et al (1995), Staudt (1997), Donald et al (2002), Fisher et al (2004, Kozma et al (2009), Molnar et al (2007) who studied the reaction of different grape varieties to powdery mildew disease in different countries have reported more or less the same results.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In general, results of the experiments indicated that 18.18% of tested varieties were immune to the disease, 13.63% were highly resistant, 9.10% were resistant, 9.10% were tolerant, 36.36% were susceptible and 13.63% highly susceptible to powdery mildew disease (Table 1). Results of our study and the differences in the reaction of varieties to powdery mildew disease are in agreement with those of previous studies (Barker et al, 2005;Eibach et al, 2007;Korbuly, 1999;Li, 1993;Wan et al, 2007). Voytovich (1987), Wang et al (1995), Staudt (1997), Donald et al (2002), Fisher et al (2004, Kozma et al (2009), Molnar et al (2007) who studied the reaction of different grape varieties to powdery mildew disease in different countries have reported more or less the same results.…”
Section: Resultssupporting
confidence: 93%
“…Monogenic resistance to E. necator has been studied in Muscadinia spp. and its hybrids with Vitis vinifera (Korbuly, 1999;Kozma et al, 2009;Molnar et al, 2007;Pauquet et al, 2001). In the Vitis genus, resistance appears to be due to several genes (Fisher et al, 2004).…”
Section: Introduction 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other resistance loci, Ren1 was found in V. vinifera and not in a wild Vitis species. It was discovered in the Asian table grape varieties 'Dhandzhal Kara' [92] and 'Kishmish vatkana' [93], which show complete resistance to powdery mildew [94]. Hoffman et al [59] and Coleman et al [95] described that the resistance conferred by Ren1 behaves as a Mendelian monogenic trait.…”
Section: Ren1mentioning
confidence: 99%